2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487430
|View full text |Cite
|
Sign up to set email alerts
|

Development and experimental validation of a minimalistic shape-changing haptic navigation device

Abstract: This paper presents a minimalistic handheld haptic interface designed to provide pedestrian navigation assistance via the intuitive and unobtrusive stimulus of shapechanging. The new device, named the Haptic Taco, explores a novel region of robotic interfaces which we believe to have benefits over other communication methods. In previous work, we demonstrated the use of a 2DOF shape changing interface for navigation without the use of sight. In this paper we seek to explore the potential of minimal 1DOF interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In that work, the 1DOF shape-changing Haptic Lotus device utilized a simple potential-field based 'hotter/colder' proximity based navigation scheme to guide users to regions of looping audio. Rudimentary localization and limited haptic feedback resolution restricted navigational and storytelling capabilities [21], though we later demonstrated that 1DOF feedback could be used effectively for navigation [22]. Flatland implements numerous technical elements to improve performance over The Question, regarding localization resolution, user co-ordination, user-centric audio triggering and haptic feedback.…”
Section: A Immersive and Inclusive Theatre Experiencesmentioning
confidence: 96%
See 1 more Smart Citation
“…In that work, the 1DOF shape-changing Haptic Lotus device utilized a simple potential-field based 'hotter/colder' proximity based navigation scheme to guide users to regions of looping audio. Rudimentary localization and limited haptic feedback resolution restricted navigational and storytelling capabilities [21], though we later demonstrated that 1DOF feedback could be used effectively for navigation [22]. Flatland implements numerous technical elements to improve performance over The Question, regarding localization resolution, user co-ordination, user-centric audio triggering and haptic feedback.…”
Section: A Immersive and Inclusive Theatre Experiencesmentioning
confidence: 96%
“…From this data, measures of motion efficiency, average velocity, the time that users faced their current target and rates of improvement were all determined. We have used measures of motion efficiency, average walking velocity and time facing the target in past work to compare Animotus performance against other haptic navigation devices [14], [15], [64]. Note that there are no standardized metrics for evaluating navigation ability with tools such as the Animotus.…”
Section: Motion Evaluationmentioning
confidence: 99%
“…In a subsequent study, Spiers et al [13] introduced the 'Haptic Taco' and compared this device to their earlier developed 'Haptic Lotus'. Both these devices have only 1DOF, namely expansion to indicate proximity.…”
Section: Autonomous Devices For Indoor Usementioning
confidence: 99%
“…Another method includes devices that change shape to provide directional clues [ 38 ]. For example, Spiers et al proposed a cube-like device with a top section that rotates and extends, providing tactile feedback on various finger areas to indicate direction [ 38 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%